Clinical analysis of primary nephrotic syndrome complicating anemia - Xing Chen; Xiaoyu Liu; Zhen Feng; Zhijuan Hu; Kai Niu; Bing Liu (Journal of International Medical Research, 2025)
Objective Anemia is the most common complication in patients with adult primary nephrotic syndrome. However, research on anemia in patients with adult primary nephrotic syndrome is limited. Our study aimed to explore the clinical characteristics and relevant factors of anemia in patients with adult primary nephrotic syndrome. Methods In total, 150 patients with primary nephrotic syndrome, who were followed up in the nephrology department of Hebei General Hospital from 2018 to 2021, were included. The patients were divided into baseline anemia and baseline no anemia groups. The clinicopathologic indices of anemia between the two groups were compared for screening the independent risk factors for anemia. Results Of the 150 patients with primary nephrotic syndrome, 34 had anemia, including 31 (20.67%) with mild anemia, 3 (2.00%) with moderate anemia, 25 (16.67%) with normocytic anemia, 3 (2.00%) with simple microcytic anemia, and 6 (4.00%) with microcytic hypochromic anemia. Diastolic blood pressure, albumin level, prealbumin level, estimated glomerular filtration rate, total cholesterol, triglyceride level, and habitual alcohol consumption were lower in the baseline anemia group than in the other group (p   <   0.05). The results demonstrated that albumin level (odds ratio = 0.838, 95% confidence interval: 0.713–0.986, p   =   0.033), prealbumin level (odds ratio = 0.838, 95% confidence interval: 0.722–0.966, p   =   0.015), total cholesterol (odds ratio = 0.544, 95% confidence interval: 0.399–0.742, p < 0.001), and habitual alcohol consumption (odds ratio = 0.119, 95% confidence interval: 0.019–0.740, p   =   0.022) were independent risk factors for baseline anemia in patients with primary nephrotic syndrome. Conclusion Patients with adult primary nephrotic syndrome have a high prevalence of comorbid anemia, mainly mild anemia and normocytic anemia. Reduced albumin, prealbumin, and total cholesterol and the absence of habitual alcohol consumption were independent risk factors for baseline anemia in patients with adult primary nephrotic syndrome.